Three Phase Flash Calculations Using Genetic Algorithm Approach - Vakili-Nezhaad, G.R.; Vahidipour, S.M.; Dargahi, M. (Asian Journal of Chemistry, 2011)
A new approach based on the genetic algorithm has been proposed for solving three phase flash calculations containing two liquid phases and one vapour phase. Based on this approach choosing the initial guess for the compositions of the involved phases is not an important step, which in the ordinary three phase algorithms affects directly the convergence of the calculations. A real problem has been solved with this approach and good results have been obtained in comparison with the experimental data. f-f approach has been adopted for vapour-liquid-liquid equilibrium (VLLE) calculations based on Peng-Robinson equation of state.